Changes in Birth Seasonality in East and West Germany, 1946-2017 - Risto Conte Keivabu (Comparative Population Studies)
Seasonal trends in fertility are found in several contexts and are affected by societal and environmental factors. This paper documents how birth seasonality in East and West Germany changed over time and, in particular, after 1989 and the onset of Reunification. We use birth counts by month from the Human Fertility Database, broken down into East and West Germany, from 1946 to 2017. We observe similar birth seasonality in East and West Germany in the years from 1946 to the 1970s, with an initial peak occurring in the first months of the year followed by a second peak in September. In the 1970s, West Germany starts to diverge, with the emergence of a single peak in births in late summer. Shortly after Reunification, the seasonal fertility trends found in West Germany are mirrored in East Germany. Consequently, it appears that the socioeconomic, cultural and institutional differences in the two areas have potentially influenced the intra-annual distribution of births, as well as the timing and number of children as described in previous studies.